Student Association of Anak Darul Ta'zim (ISKANDAR) organises Iskandar on Tour 5.0 programme - Norul Fadilah, Abdullah (UMPSA, 2024)
JOHOR BAHRU, 19 May 2024 – A total of 50 members of the Student Association of Anak Darul Ta’zim (ISKANDAR) Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised the Iskandar on Tour 5.0 programme in Johor Darul Takzim.